PENGARUH SISTEM PELAYANAN BANK SYARIAH INDONESIA SAROLANGUN TERHADAP KEPUASAN NASABAH - Pebiola; Suhar; Muhammad Ismail (Universitas Sains dan Teknologi Komputer, 2023)
At this time, as we know, conventional banks are very superior compared to Islamic banks, therefore Islamic banks are always intensive in service quality to increase customer satisfaction. Bank Syariah Indonesia, the Sarolangun branch, always makes improvements to service for customers in various ways. Currently, Bank Syariah Indonesia Sarolangun is very concerned about the quality of bank services, which is to see how much customer satisfaction is for the services performed by the bank. Events that have occurred at the Indonesian Islamic bank Sarolangun where some of the customers on the bank's side experienced services that were a little detrimental to customers, therefore in this study to try to see how the quality of service performed by the bank whether the services provided were satisfying or vice versa. Does the service quality of the Indonesian Islamic bank sarolangun affect customer satisfaction which has experienced poor and unsatisfactory service by the customer. This is a field research (field research) descriptive quantitative approach using the charter method to measure customer satisfaction with the bank, this research is through validity testing, reliability testing, classical assumption testing and simple linear regression testing by managing the data of several numbers obtained from the questionnaire and then describe and conclude the results of these data in order to determine the significant relationship of service quality to measure customer satisfaction